Microbial Diversity Reduction in Soil by Long-Term Climate Warming. (15th September 2022) - Dave, Mayank; Panwar, Kartika; Dadhich, Itika; Sharma, Yagya; Malodia, Anupriya; Shaik, Nagaraju
Abstract : Global environmental changes are altering where species dwell and how they interact with one another. Organisms exist in intricate communities with thousands of different species, some of which are beneficial, some of which are destructive, and others of which have no influence at all. Because natural communities are made up of organisms with widely disparate life histories and modes of change, it is improbable that they will all react in the same manner to changes in the environment. The consequences of global change on interactions between plants and herbivores and plants and pollinators have been extensively reported. Less attention has been made to the interactions of soil bacteria and plants, as well as soil microorganisms. Because soil microorganisms govern how nutrients vary, feed nutrients to plants, allow neighbours to cohabit, and manage plant populations, changes in how soil microorganisms and plants interact may have a significant impact on the sorts of plants in an ecosystem and how it operates. This study investigates how soil interactions impact soil bacteria and how they interact with one another, both directly and indirectly. It also covers novel and fascinating areas of inquiry, as well as the implications that changes in these relationships have on the makeup and operation of ecosystems.